Metformin and Its Benefits for Various Diseases - Lv, Ziquan; Guo, Yajie (Frontiers in Endocrinology, 2020)
Metformin is a widely used biguanide drug due to its safety and low cost. It has been used for over 60 years to treat type 2 diabetes at the early stages because of its outstanding ability to decrease plasma glucose levels. Over time, different uses of metformin were discovered, and the benefits of metformin for various diseases and even aging were verified. These diseases include cancers (e.g., breast cancer, endometrial cancer, bone cancer, colorectal cancer, and melanoma), obesity, liver diseases, cardiovascular disease, and renal diseases. Metformin exerts different effects through different signaling pathways. However, the underlying mechanisms of these different benefits remain to be elucidated. The aim of this review is to provide a brief summary of the benefits of metformin and to discuss the possible underlying mechanisms.